Responses to Sedimentation in Ramet Populations of the Clonal Plant Carex brevicuspis - Pan, Bai-Han; Xie, Yong-Hong; Li, Feng; Zou, Ye-Ai; Deng, Zheng-Miao (Frontiers in Plant Science, 2018)
In aquatic ecosystems, sedimentation is an important factor that affects plant growth, mainly due to sediment depth. Clonal morphological plasticity is an effective strategy in clonal plants for acclimatization to sediment burial. To date, few studies have examined growth responses to sedimentation on the clonal plants at the ramet population level. This study aimed to explore the interactive effects of population size and burial depth on growth and clonal morphology of Carex brevicuspis. Three population sizes (2, 8, and 32 ramets) and 3 burial depths (0 cm, 5 cm, and 10 cm) were used in this experiment. Under shallow (5 cm) and deep (10 cm) burial conditions, biomass accumulation and relative growth rate (RGR) were lower than in the no burial treatment (P < 0.05). RGR of the small and medium populations was especially high compared to the large populations (P < 0.05). Biomass allocation was higher to belowground parts than aboveground parts, except for the small populations in the 5 cm burial treatments. Both shallow burial and smaller populations led to more biomass being allocated to aboveground parts. Deep burial elongated the 1st order spacer more than shallow burial, and sedimentation had negative effects on the 2nd order spacer length. The number of new ramets did not decrease in the 5 or 10 cm burial treatments compared to the unburial treatment, and larger populations usually had more ramets than smaller ones; the proportion of clumping ramets was higher than the proportion of spreading ramets, and deeper burial and smaller populations led to higher proportions of spreading ramets. These results indicated that the growth of C. brevicuspis was limited by sediment burial at the ramet population level. Smaller populations enable C. brevicuspis to adjust its escape response to burial stress, may allow this species to effectively survive and widely distribute in Dongting Lake wetland.